Effects of Dose, Age, Sex, Body Weight, and Smoking on Plasma Concentrations of Olanzapine and N-desmethyl Olanzapine in Inpatients With Schizophrenia. Issue 3 (23rd May 2021) - An, Huimei; Fan, Hongzhen; Chen, Song; Qi, Siyuan; Ma, Botao; Shi, Jing; Wang, Zhiren; Yang, Fude
Abstract: Purpose: This study aimed to investigate the combined effects of dose, age, sex, body weight, and smoking on plasma concentrations of olanzapine (OLA) and N-desmethyl olanzapine (DMO) in Chinese inpatients with schizophrenia. Methods: A retrospective study including 185 inpatients was conducted. The steady-state plasma concentrations of OLA (COLA ) and DMO (CDMO ) were measured using high-performance liquid chromatography-tandem mass spectrometry. The combined effects of dose, age, sex, body weight, and smoking on COLA and CDMO were evaluated. Findings: Multiple linear regression analyses revealed that dose, age, body weight, and smoking had significant effects on COLA and CDMO in inpatients with schizophrenia treated with OLA. The dose was the most important determinant of COLA and CDMO and was positively correlated with both. Furthermore, smokers exhibited a significantly lower COLA and COLA + DMO, whereas higher body weight led to the reduction of COLA, CDMO, and COLA + DMO . Advanced age was associated with lower CDMO . Implications: These results suggest that dose, age, body weight, and smoking have a significant influence on the plasma concentration of OLA and its metabolite DMO. Clinicians should consider the combined effects when prescribing OLA to patients with schizophrenia.